Literature Literacy as a Medium of Peace and Harmony Between Two Countries - Noor, N M (KnE Social Sciences, 2018)
Literary tradition in Malaysia middle/high school from the very beginning to the era of Literary Component in Malay language (Komsas) plays a big role in shaping the intellectuality of student’s mindset. It is carried out by introducing novels around the Archipelago that corresponds to time and issues, without leaving the main theme of universal humanity. These themes have not changed. That is the purpose of literature subjects being introduced in school. Since the 70s, students in Malaysia have been exposed to Indonesian ’heavy’ novels such as Di bawah Lindungan Kaabah by HAMKA, Salah Asuhan by Abdul Moeis, followed by Atheis by Achdiat Karta Mihardja and Keluarga Gerilya by Pramoedya Ananta Toer and poems by Amir Hamzah and Chairil Anwar All the novels, poems and short stories reveal the valuable aspect and their impact in forming the student’s mind. Just take an example of the novel Atheist that features the soul of a traditionalist Islamist to face all modern ideologies that arose post Second World War. Or take another example of a patriotic struggle by characters like Saaman from Amila’s family in Keluarga Gerilya. These are the serious issues that we could learn by reading Indonesia literary works by a few great writers. Therefore, Indonesian literature has played an important role in Malaysia as a medium of peace and harmony. Keywords: peace, harmony, universal humanity